1995
DOI: 10.1080/00140139508925148
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among visual display terminal workers: individual, ergonomic, and work organizational factors

Abstract: A number of individual, ergonomic, and organizational factors of presumed importance for the occurrence of musculoskeletal disorders were investigated in a group of 260 visual display terminal (VDT) workers. The cross-sectional study utilized medical and workplace investigations as well as questionnaires. The results were subjected to a multivariate analysis in order to find the major factors associated with various upper-body muscular problems. Several such factors were identified for each investigated type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
211
2
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(239 citation statements)
references
References 0 publications
20
211
2
6
Order By: Relevance
“…For example, no association was observed with increasing time spent working with a VDU or with frequent mouse use, although two systematic reviews, including prospective studies, found convincing evidence of an increased risk of UE musculoskeletal symptoms associated with exposure to these factors 34,35) . Inadequate duration of breaks and poor supervisor support were not retained in the fully adjusted models, despite other studies finding that they consistently increased the risk of UE symptoms among CC and other office workers 10,36,37) . Also, noise exposure has never been linked, to our knowledge, to UEMSD risk, but it has been observed that the frequent presence of sudden sounds and operators' voices in CCs may act as a psychological stressor, because it makes it more difficult to understand clients during telephone 6,38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, no association was observed with increasing time spent working with a VDU or with frequent mouse use, although two systematic reviews, including prospective studies, found convincing evidence of an increased risk of UE musculoskeletal symptoms associated with exposure to these factors 34,35) . Inadequate duration of breaks and poor supervisor support were not retained in the fully adjusted models, despite other studies finding that they consistently increased the risk of UE symptoms among CC and other office workers 10,36,37) . Also, noise exposure has never been linked, to our knowledge, to UEMSD risk, but it has been observed that the frequent presence of sudden sounds and operators' voices in CCs may act as a psychological stressor, because it makes it more difficult to understand clients during telephone 6,38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…There is some longitudinal evidence to suggest that low back pain during childhood is a risk factor for low back pain in adulthood (Harreby et al 1995). Whilst computer-related musculoskeletal discomfort is also prevalent higher up in the spinal column and in the upper extremities (Hu¨nting et al 1981, Faucett and Rempel 1994, Bergqvist et al 1995, Sillanpa¨a¨et al 2003, similar principles are likely to apply.…”
Section: Child Computer Use May Impact On Adult Risk/ Computer Usementioning
confidence: 94%
“…Pain and musculoskeletal discomfort have been associated with computer use by adult populations (Bergqvist et al 1995, Marcus et al 2002 and there are indications that this may also be an issue for college students (Katz et al 2000, Mene´ndez et al 2007) and younger children (Harris and Straker 2000, Jacobs and Baker 2002, Williams 2002, Szeto 2003, Straker et al 2006a. Hakala et al (2006) conducted a survey study of 6003 Finnish children aged 14, 16 and 18 years.…”
Section: Musculoskeletal Problemsmentioning
confidence: 99%
“…The continuous activation of muscles of the arms, shoulder girdle, neck and trunk to maintain a quasi-static position to allow the hands and arms to operate the keyboard has been proposed as one of the causal factors of neck/ shoulder and arm/hand diagnoses (Bergqvist et al, 1995).…”
Section: Introductionmentioning
confidence: 99%